2016
DOI: 10.1038/srep37362
|View full text |Cite
|
Sign up to set email alerts
|

Bright blue-shifted fluorescent proteins with Cys in the GAF domain engineered from bacterial phytochromes: fluorescence mechanisms and excited-state dynamics

Abstract: Near-infrared fluorescent proteins (NIR FPs) engineered from bacterial phytochromes (BphPs) are of great interest for in vivo imaging. They utilize biliverdin (BV) as a chromophore, which is a heme degradation product, and therefore they are straightforward to use in mammalian tissues. Here, we report on fluorescence properties of NIR FPs with key alterations in their BV binding sites. BphP1-FP, iRFP670 and iRFP682 have Cys residues in both PAS and GAF domains, rather than in the PAS domain alone as in wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 62 publications
(131 reference statements)
2
25
0
8
Order By: Relevance
“…Because the BphP-derived miRFP670, mIFP and miRFP703 already exhibit the efficient binding of endogenous chromophore, future engineering efforts on these NIR FPs should focus on an increase of their quantum yields, e.g., via reduction of various excited-state deactivation pathways (Hontani et al, 2016). In contrast, the APCα-derived smURFP should be further evolved to substantially enhance its efficiency and specificity to bind endogenous BV chromophore in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because the BphP-derived miRFP670, mIFP and miRFP703 already exhibit the efficient binding of endogenous chromophore, future engineering efforts on these NIR FPs should focus on an increase of their quantum yields, e.g., via reduction of various excited-state deactivation pathways (Hontani et al, 2016). In contrast, the APCα-derived smURFP should be further evolved to substantially enhance its efficiency and specificity to bind endogenous BV chromophore in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that in BphP1 FP, BV could be linked to Cys GAF via C3 1 or C3 2 carbon atoms of the pyr role ring A side chain, both chromophore derivatives being spectrally identical [27]. Two suggestions have been made to explain the high quantum yield of NIR FPs with the fluorescence spectra displaying hypsochromic shift: (i) the chromophore bound to Cys GAF has more rigid structure due to the limited mobility of the pyrrole ring A; (ii) mobility of the ring A does not affect the properties of BV Cys GAF , because in this case, it is not included in the conjugated system of π bonds [47]. Chromophore inter action with dimeric NIR FPs is complicated by inter monomer allosteric effect, with a number of spectral characteristics being sensitive to this effect.…”
Section: Molecular Engineering Of Nir Fpsmentioning
confidence: 99%
“…BphP1-FP, iRFP670 and iRFP682 proteins, in addition to conserved Cys20 in the PAS domain, contain Cys residue in the conserved SPXH amino acid motif of the GAF domain (Cys253). NIR FPs with this additional Cys are blue-shifted, exhibit higher quantum yield and longer fluorescence lifetimes [ 27 , 109 , 110 ]. It was shown that mutants of such double-Cys NIR FPs, containing a single Cys either in the PAS or in the GAF domains, demonstrate different spectral properties.…”
Section: Engineering Approaches To Develop Near-infrared Fluorescementioning
confidence: 99%
“…These findings made possible the rational design of brighter and spectrally distinct NIR FPs and were successfully applied to engineer spectrally distinct monomeric miRFPs [ 35 ]. In BphP-derived NIR FPs, the covalent binding of BV to Cys residue in the GAF domain via C3 1 and C3 2 chromophore atom leads to restricting ring A motion, resulting in a substantial increase of quantum yield [ 109 ]. Interestingly, these NIR FPs bind Cys in the GAF domain similarly to CBCRs, which also bind chromophore through C3 1 carbon of ring A.…”
Section: Engineering Approaches To Develop Near-infrared Fluorescementioning
confidence: 99%
See 1 more Smart Citation